2010
DOI: 10.1063/1.3489899
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, magnetic, optical, and electrical transport properties of the nanocomposites of polyaniline with some rare earth chlorides

Abstract: Nanocomposites of polyaniline with some rare earth chlorides like neodymium chloride, europium chloride, and dysprosium chloride were synthesized by chemical oxidative polymerization of aniline. Morphological, structural, thermal, optical, magnetic, and electrical properties of the samples were characterized by scanning electron microscope, x-ray diffractometer, Fourier transform infrared spectrometer, thermogravimetric analyzer, differentiating scanning calorimeter, optical absorption spectroscopy, room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…As such, thermally converted GNDs should share both diamond and graphitic characteristics. The XRD pattern of PANI also displayed characteristic peaks of conducting form in line with the literature. , The prominent peaks for PANI (e.g., 20.6 (020), 25.4 (220), 26.6 (111), 27.13 (121), and 35.4° (201)) were clearly evident in the XRD pattern. The XRD patterns of GND/PANI and GND/PANI/urease confirmed that the crystal structure of PANI was not affected by the incorporation with GNDs and further by the immobilization of urease, respectively.…”
Section: Resultssupporting
confidence: 86%
“…As such, thermally converted GNDs should share both diamond and graphitic characteristics. The XRD pattern of PANI also displayed characteristic peaks of conducting form in line with the literature. , The prominent peaks for PANI (e.g., 20.6 (020), 25.4 (220), 26.6 (111), 27.13 (121), and 35.4° (201)) were clearly evident in the XRD pattern. The XRD patterns of GND/PANI and GND/PANI/urease confirmed that the crystal structure of PANI was not affected by the incorporation with GNDs and further by the immobilization of urease, respectively.…”
Section: Resultssupporting
confidence: 86%
“…Interestingly, our PANI/SBA‐15 material exhibited good conductivity and electrocatalytic activities (see below), presumably because of the low degree of branching or cross‐link density of its PANI. This was corroborated by wide‐angle X‐ray diffraction (XRD) analysis (see Supporting Information), which showed the PANI to have an amorphous or nanoscale structure, suggesting the presence of low cross‐link density in it (please note that bulk PANI materials with high degree of branching and high cross‐link density, e.g., prepared by magnetic stirring of aniline in solutions, typically show sharp Bragg reflections) 32–35…”
Section: Methodsmentioning
confidence: 73%
“…XRD patterns of poly aniline samples that observed in figure 2.a, 2 characteristic peak of poly aniline near 2θ= 15 ˚, 25 18.9˚,this peaks manifest emeraldine salt form of PANI, the crystallinity of PANI can be ascribed to the repetition of benzenoid and quinoid ringsin PANI chains. But the XRD pattern of PC5 sample show sharp and well defined peaks at 2θ= 37.9˚, 44.1˚, 64.4˚ and 77.6˚ of the synthesized poly aniline sample that reveal the higher degree of crystallinity [10,13]. XRD patterns of polyaniline samples derived from aniline monomer indicated that the PANI super morphology depend on acidity of reaction media for the oxidation of aniline monomer by APS as oxidant due to the aggregation of PANI nanoparticles from pH value 2 Degree to pH 5 degree to form elongated PANI nanoparticles, PANI nanotube and PANI rod.…”
Section: Resultsmentioning
confidence: 99%
“…XRD of PANI that produce in the oxidation of aniline monomer by APS oxidant with strong acid medium (sulfuric acid) show the crystallinity of PANI decrease at 2θ= 37.8˚, 44˚, 64.5˚ and 77.5˚ compare to the formation of PANI from aniline monomer in acetic acid reaction medium, but in case of production of PANI nanoparticles from aniline monomer in alkali (sodium hydroxide) reaction medium exhibit higher crystallinity with formation of nanoparticles without aggregate of nanoparticles to form super morphology of PANI Nano particles [10]. XRD patterns that observed produce with the oxidation of aniline hydrochloride monomer by APS oxidant in aqueous or acetic acid reaction medium are less amorphous than the pattern of PANI that obtained by the oxidation of aniline hydrochloride monomer in presence of strong acid (sulfuric acid) reaction medium.…”
Section: American Journal Of Appliedmentioning
confidence: 99%
See 1 more Smart Citation